2014
DOI: 10.1364/oe.22.024817
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the performance of the light field microscope using wavefront coding

Abstract: Light field microscopy has been proposed as a new high-speed volumetric computational imaging method that enables reconstruction of 3-D volumes from captured projections of the 4-D light field. Recently, a detailed physical optics model of the light field microscope has been derived, which led to the development of a deconvolution algorithm that reconstructs 3-D volumes with high spatial resolution. However, the spatial resolution of the reconstructions has been shown to be non-uniform across depth, with some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 23 publications
1
102
0
Order By: Relevance
“…Further improvements to the system hardware could also include the use of phase mask in front of the camera. Combined with a reliable estimate of the modified PSF, this has been shown to be effective in improving deconvolved light field images close to the native object plane [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further improvements to the system hardware could also include the use of phase mask in front of the camera. Combined with a reliable estimate of the modified PSF, this has been shown to be effective in improving deconvolved light field images close to the native object plane [28].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Nevertheless, it has been shown that cubic and trefoil-shaped phases are most used to achieve high-quality images when spherical aberration, 10,11) astigmatism 14,15) and high orderaberrations 15) are also present in the system. WFC can be found in many different applications such as in ophthalmic optics, [15][16][17] iris recognition, 18,19) complexity reduction in optical systems, 20) control of thermal defocus in infrared systems, 21) barcode reading, 22) and microscopy, 23) among many others. The DOF in each application can be extended by a trefoil phase at the exit pupil of the optical system, and the trade-off between the DOF and the image resolution properties is dependent on the peak-to-valley value (strength) of the phase.…”
Section: Introductionmentioning
confidence: 99%
“…For example, wavefront coding has been used for extending the depth of focus with a cubic phase mask. [1][2][3] The application of our work is to reduce the risk of laser damage from coherent laser sources. In a traditional imaging system, a distant laser source will be focused onto the focal plane of the optical system.…”
Section: Introductionmentioning
confidence: 99%